2020
DOI: 10.31616/asj.2019.0055
|View full text |Cite
|
Sign up to set email alerts
|

Is Scapular Stabilization Exercise Effective for Managing Nonspecific Chronic Neck Pain?: A Systematic Review

Abstract: Scapular stabilization is thought to have an important role in improving pain and dysfunction around the neck and shoulders, but evidence of this is lacking. We aim to systematically review the effect of a scapular stabilization exercise (SSE) on pain and dysfunction in patients with nonspecific chronic neck pain (NP). We searched the PubMed, EMBASE, CINAHL, and Cochrane Library databases using the terms (NP [MeSH] OR NP OR cervical pain OR neck ache OR cervicalgia) AND (scapular exercise OR periscapular exerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…The optimal frequency and duration of the exercises, in addition to the importance of their supervision, are not known [18]. In most previous studies, the intervention time ranges from 4 weeks to a year with a frequency between 2 and 3 times per week [42]. The obtained results in this research, using a six week supervised program and frequency of 2 days per week, appears to be consistent with programs analyzed in the scientific literature.…”
Section: Discussionsupporting
confidence: 81%
“…The optimal frequency and duration of the exercises, in addition to the importance of their supervision, are not known [18]. In most previous studies, the intervention time ranges from 4 weeks to a year with a frequency between 2 and 3 times per week [42]. The obtained results in this research, using a six week supervised program and frequency of 2 days per week, appears to be consistent with programs analyzed in the scientific literature.…”
Section: Discussionsupporting
confidence: 81%
“…Scapular stabilization exercises focused on enhancing periscapular muscles, such in serratus anterior, middle, lower trapezius muscles. 39 In the current study, NDI showed a statistical significant decrease at pre and post intervention in both the groups. The primary outcomes of this study showed that both exercise programs showed a significant increase in CVA, leading to improvement in FHP.…”
Section: Discussionsupporting
confidence: 53%
“…It has been reported that the activity of the scapular muscles decreases with the change of cervical posture in some cervical problems (7)(8)(9). For this reason, in addition to the decrease in the activation of the scapular muscles in SIS, the stability of the cervical region may also be negatively affected due to the relationship of the shoulder and spine.…”
Section: Introductionmentioning
confidence: 99%